Piezoresistive polymer-based materials for real-time assessment of the stump/socket interface pressure in lower limb amputees - Ferreira, Armando José Barros (2017)
The present work reports a suitable piezoresistive Carbon Nanotubes / poly(vinylidene fluoride) - CNT/PVDF composite capable of measuring the interface pressure within prosthetic stump/sockets. The transducers were prepared by hot pressing with CNT, with sample concentrations up to 10 wt.%. The sensibility (Gauge Factor) of the composites was characterized using a mechanical testing equipment and the values reached 6.2. After the optimization of the materials, tests were conducted with a prototype placed in lower limb amputee patients, performing several standing and walking protocols. The prototype was tested in four lower limb amputees using a CNT concentration of 2 wt.% within the PVDF matrix. The transducers were fabricated with dimensions of 10×25 mm2 and ~1mm of thickness functionalized with Ti-Ag thin film electrodes at the surface. To acquire the electrical signal, an electronic circuit was developed with a wireless data acquisition system. The results suggest a strong application potential of the developed sensor prototype, namely as a complementary diagnostic tool, supporting socket design and rectification, being therefore an effective mean to increase patients’ quality of life.